Contributions to the Lepanthes (Orchidaceae) knowledge in Ecuador: A new species from Cordillera del Toisán and new records for the country - Monteros, Marco F.; Restrepo, Eugenio; Iturralde, Gabriel A.; Jiménez, Marco M.; Baquero, Luis E. (Phytotaxa, 2023)
Río Manduriacu and Dracula reserves, owned by the Fundación EcoMinga, are located in northwestern Ecuador, which has been a hotspot for the discovery of numerous new orchid species in recent years. Here, we propose Lepanthes inesmanzanoae, a new species found in Río Manduriacu reserve in Cordillera del Toisán. This species is distinguished by the transversely bilobed, velvety petals with a minute process on the outer margin of the midvein, the lower lobe of the petal shorter, triangular, attenuate, the appendix triangular, acute and the bilobed stigma. The new taxon is described, illustrated, and compared to its most similar species. Additionally, we report four new records of the genus Lepanthes for Ecuador.